The Neural Basis of Reading - Cornelissen, P; Hansen, P; Kringelbach, M; Pugh, K (Oxford University Press, 2010)
Reading is a unique human skill, and modern societies rely extensively on literacy skills. Reading disability can therefore have a profound personal, economic, and social impact. However, the scientific understanding of the neural basis of reading in the normal brain is underdeveloped. A better understanding of normal reading processes could help individuals with developmental dyslexia and those with reading disabilities gained through injury or disease. Neuroimaging offers a unique window on reading and has allowed us to reach interesting insights about the neural correlates of reading in health and disease. It has also raised questions for scientific debate. The whole field of reading research is very much a dynamic and growing one. This book provides some seasoned insights and to offer a window into various conceptual and technical issues that continue to be discussed and developed.